2023
DOI: 10.1021/accountsmr.2c00260
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Catalytic Nanocrystals: From Model Catalysts to Efficient Catalysts

Abstract: Conspectus Solid catalysts play a key role in the chemical industry, energy, and the environment. Fundamental understanding of heterogeneous catalysis exerted by solid surfaces is useful for structural designs of efficient catalysts but is challenging due to the complexity. Emerging uniform catalytic nanocrystals (NCs) with controlled and well-defined surface structures have brought new opportunities for fundamental understanding and directed explorations of efficient catalysts. In a previous Account (Acc. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…[12][13][14][15][16] Yet, the complex network of reactions in DEP often precludes Cu or Cu 2 O catalysts from reaching optimal activity and selectivity by themselves. [17][18][19] In this regard, the introduction of organic and inorganic additives would open new dimensions to optimize the catalytic performance. Specifically, halogens such as fluorine (F), chlorine (Cl), bromine (Br), and iodine(I) ions have proven to be exceptionally effective modulators of catalyst behaviours for olefin epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Yet, the complex network of reactions in DEP often precludes Cu or Cu 2 O catalysts from reaching optimal activity and selectivity by themselves. [17][18][19] In this regard, the introduction of organic and inorganic additives would open new dimensions to optimize the catalytic performance. Specifically, halogens such as fluorine (F), chlorine (Cl), bromine (Br), and iodine(I) ions have proven to be exceptionally effective modulators of catalyst behaviours for olefin epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically dispersed Cu–O–Zr sites were reported to exclusively catalyze the reverse water gas-shift (RWGS) (CO 2 (g) + H 2 (g) = CO­(l) + H 2 O­(l)) reaction, whereas the monatomic dispersed Cu 1 /ZrO 2 catalyst achieved 100% methanol selectivity in CO 2 hydrogenation . CO 2 hydrogenation to methanol over ZrO 2 –Cu based catalysts was proposed via the RWGS+CO-Hydro pathway or formate pathway. ,,, Additionally, the phase of ZrO 2 also profoundly affected the catalytic performance of ZrO 2 –Cu-based catalysts in CO 2 hydrogenation. ,, The Cu facet was extensively reported to influence the catalytic performance of Cu-involved catalysts but has not been reported for ZrO 2 –Cu catalysts in the CO 2 hydrogenation reaction. Meanwhile, we found that temporal in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was able to study elementary surface reaction kinetics of catalytic reactions involving stable surface intermediates, such as formate species during CO or CO 2 hydrogenation reactions .…”
mentioning
confidence: 99%